What Does a Modern Anatomist Look like? Current Trends in the Training of Anatomy Educators. Issue 3 (13th September 2018) - Schaefer, Audra F.; Wilson, Adam B.; Barger, J. Bradley; Azim, Homaira M.; Brokaw, James J.; Brooks, William S.
Abstract : Anatomical sciences are foundational to the health professions, yet little is known about the qualifications of anatomy educators at the graduate and professional level in the United States. Moreover, there is concern that the number of qualified anatomy educators being trained may be insufficient to meet the growing demand posed by new and expanded programs in medicine and allied health specialties. The authors surveyed anatomists from across the country to (i) characterize the educational credentials of current anatomy educators and (ii) assess the perceived need for education‐focused postdoctoral positions or formal mentorships to prepare anatomists for teaching‐intensive faculty positions. To probe the survey responses more deeply, one‐on‐one interviews were conducted with eight individuals selected to represent a diverse sample of respondents in terms of institution, gender, and academic rank. Results indicate that 30–40% of educators at the graduate level and approximately 60% of those at the undergraduate level lack graduate coursework in histology, embryology, and neuroanatomy. Forty‐five percent of respondents had completed a postdoctoral fellowship. Eighty‐six percent replied "yes/maybe" to the question of whether an anatomy education postdoctoral fellowship would benefit doctoral graduates. The top 3 reasons for this recommendation were to (i) establish independent educational research, (ii) improve a publication record, and (iii) gain additional teaching experience. Notable weaknesses of education‐focused postdoctoral training were related to finances, fear of exploitation, and undervaluing of teaching. Moving forward, postdoctoral fellowships and other forms of postgraduate training may represent a key strategy for training anatomists in the current educational climate. Anat Sci Educ 00: 000–000. © 2018 American Association of Anatomists.